Cyclical Patterns of Government Expenditures in Sub-Saharan Africa : Facts and Factors - Yackovlev, Irene; Gadenne, Lucie; Lledo, Victor (Washington, D.C. : International Monetary Fund, 2009)
This paper documents cyclical patterns of government expenditures in sub-Saharan Africa since 1970 and explains variation between countries and over time. Controlling for endogeneity, it finds government expenditures to be slightly more procyclical in sub-Saharan Africa than in other developing countries and some evidence that procyclicality in Africa has declined in recent years after a period of sharp increase through the 1990s. Greater fiscal space, proxied by lower external debt, and better access to concessional financing, proxied by larger aid flows, seem to be important factors in diminishing procyclicality in the region. The role of institutions is less clear cut: changes in political institutions have no impact on procyclicality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet